An Analysis of Haryo Pamungkas's Short Story ‘The Old Writer’ and Its Correlation with the Old Age of Indonesian Society - Ironika, Gerry (YASIN, 2025)
This study is motivated by a common phenomenon experienced by the elderly in Indonesia, namely the inner struggle of facing old age, the loss of identity, and social alienation, issues often overlooked in the social and emotional spheres. The purpose of this study is to analyze the short story Penulis Tua by Haryo Pamungkas and examine its correlation with the realities of elderly life in Indonesia. A qualitative approach was employed using structural and sociological literary analysis methods to uncover both the narrative meaning and social relevance of the literary text. The analysis reveals that Penulis Tua not only portrays aging as a personal experience marked by the loss of identity and role, but also represents the social condition of the elderly who are frequently neglected both economically and emotionally by those around them. The story highlights the elderly’s need for appreciation, social acceptance, and meaningful roles within the family and community. The correlation between the reality depicted in the text and the actual social conditions of the elderly in Indonesia reinforces literature’s role as a mirror of relevant social critique. The implications of this study emphasize the importance of fostering collective awareness to respect the elderly, value their contributions, and cultivate empathy toward the dynamics of aging amid ongoing social change.